2022
DOI: 10.3390/coatings12030343
|View full text |Cite
|
Sign up to set email alerts
|

High Entropy Alloys Coatings Deposited by Laser Cladding: A Review of Grain Boundary Wetting Phenomena

Abstract: High-entropy alloys (HEAs) are called also alloys without a main component or multiprincipal alloys. They consist of five, six or more components in more or less equal proportions and possess unique properties. Several dozens of thousands of publications have already been devoted to bulk HEAs, while HEA coatings are just beginning to develop. More than half of the works on the deposition of HEA coatings are devoted to laser cladding. In the laser cladding process, a mixture of powders on a substrate is melted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…The presence of two or more phases in the alloy makes it possible to observe a phenomenon known as grain boundary wetting. In case of complete grain boundary wetting one phase substitutes the grain boundaries in another phase [ 17 , 42 ]. As a result, instead of one grain boundary, two interphase boundaries are formed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of two or more phases in the alloy makes it possible to observe a phenomenon known as grain boundary wetting. In case of complete grain boundary wetting one phase substitutes the grain boundaries in another phase [ 17 , 42 ]. As a result, instead of one grain boundary, two interphase boundaries are formed.…”
Section: Discussionmentioning
confidence: 99%
“…The TiZrHfMoCrCo alloy studied in this paper belongs to promising biomaterials, its biocompatibility is comparable to commercially pure titanium, which is used for orthopedic implants. Detailed reviews on HEAs can be found in References [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Si, Nb, and Cr elements have the potential to enhance the coating's high-temperature properties on a Ti6Al4V base. High-purity raw materials are required for HEAs, and material cost and availability must be considered [7][8][9][10] . Coating thickness and structure significantly impact performance, and parameters such as grain size and lattice orientation must be controlled during preparation [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Since the high-entropy alloys (HEAs) were originally proposed by Cantor et al [1] and Yeh et al [2], there has been a growing interest in these multicomponent metallic materials. With a wide range of chemical compositions available, HEAs exhibit a variety of phase transformations, mechanical properties, and microstructural types, leading to a wealth of research publications, including numerous reviews [3][4][5][6]. Typically, HEAs consist of five or more components, with proportions ranging from 5 to 35 at.%.…”
Section: Introductionmentioning
confidence: 99%